Cardiology cathlab-based management of thrombotic carotid stenoses in acute ischaemic stroke en route to full interventional stroke service: tools, techniques, challenges and patient outcomes. (25th November 2020) - Musialek, P; Mazurek, A; Tomaszewski, T; Borratynska, A; Urbanczyk, M; Lesniak-Sobelga, A; Klecha, A; Kowalczyk, S.T; Kozanecki, A; Wilkolek, P; Drazkiewicz, T; Trystula, M; et al.
Abstract: Background: Shortage of endovascular operators able to deliver manual thrombectomy in acute ischemic stroke (AIS) on a 24/7/365 basis is a main challenge in many health care settings around the world. Another fundamental barrier is getting multispecialy teams to work collaboratively with each other in AIS as is already done (albeit on an elective rather than acute basis and in absence of "territorial" issues) in managing stroke mechanistic pathologies such as atrial fibrillation (pharmacology/ablation) or PFO (diagnosis/closure). Purpose: To establish a practical path towards a clinically and orranizationally effective cardiology cathlab-based acute ischaemic stroke service, including intracranial manual thrombectomy, in a large multi-specialty hospital with a high-volume stroke unit but absence of neuroradiology service. Methods: Withn a symptomatic and increased-stroke-risk asymptomatic carotid stenosis all-comer endovascular revascularization study (NeuroVascular Team decision-making) we have treated, on an emergent basis, 17 patients (13 men, age 58–75 years, median 67 years) with AIS caused by severe thrombotic carotid artery stenoses. All cases were performed as part of our pathway towards a full 24/7 thrombectomy stroke service. Results: All lesions (100%) were thrombotic (mobile thrombus - 29%). Proximal neuroprotection (flow reversal using a common carotid artery±external carotid artery occlusive balloon/s) was used in 15/17 patients (88%). In 2 patients (12%) filter protection was applied as proximal system use was unfeasible for anatomic or clinical reasons. All cases were done under activated clotting time control and using a micronet-covered embolic prevention stent system that was routinely optimized -under an effective neuroprotection- with large balloons/high pressures. There were no procedure- or device-related complications. TIMI/TICI-3 was achieved in all cases. Vascular access closure device use was 76%. A 30-day good clinical outcome (mRS of 0–2) rate was 94%. One patient had a haemorrhagic stroke transformation that finally led to death. By 30 days no new stroke, stent thrombosis, myocardial infarction or other SAE occurred Conclusions: Cardiologists skilled in carotid interventions are naturally positioned to deliver AIS treatment. 24/7 interventional services and networks for acute myocardial infarction have long been established and, as demonstrated in our centre, the services and skills can be translated -in collaboration with a local stroke unit/neurology- to AIS. Breaking away from traditionally-perceived "territories" towards working as a multispecialy AIS team is a logical concept that provides an effective healthcare solution for large numbers of stroke patients currently needing -and not receving- thrombectomy. Working hand in hand with neurology and radiology in managing acute carotid syndromes is thus part of a natural evolution towards full interventional stroke services including thrombectomy. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Jagiellonian University Medical College